Utvärdering av byggsektorns miljöbedömningssystem BASTA - Borefur, Maria (My University, 2006)
Abstract In the fall of 2003 a project was started in the Swedish building sector that is called BASTA (the building sectors termination of especially harmful substances). The project is operated by the building companies NCC, Skanska, PEAB and JM, the Swedish Building Industry and the Swedish Environmental Institute IVL. The purpose of the project is to create a common environmental assessment system for the entire building industry and with the help of this system phase out the use of especially harmful properties from building products. In a large sense BASTA works like this; On the BASTA web site there is a database, to which a supplier can register the company and the company s products. Only those products with a substance content that fulfil the demands of the BASTA system, is to be registered. As it is the supplier himself that carries out the registration of the company and the company s products to the system, the BASTA-organisation annually controls that the companies that are registered in the database, fulfils BASTA s demands. Since NCC is one of the companies that operates BASTA, BASTA is probably going to be the environmental assessment system that is recommended for the company in the future. At the same time NCC showed a large interest for the substance content in installation products, which made these products interesting for this master thesis work, that was carried out in co-operation with NCC Teknik in Gothenburg and Chalmers Technical University. The study evaluates BASTA through an attempt to BASTA-register three selected installation products that are frequently used in a typical building, constructed by NCC. The goal of this study was to see how well BASTA works in a real case and through that bring out the points of improvements of the system. According to the limitations and the assumptions that was made in this study, the result of the study show that no one out of the three selected installation products pass the Properties Criteria of BASTA or the Conditions of Agreement to BASTA. To a large extent this depends on the lack of information that is common on the chemical market today, together with BASTA s high set demands. The study shows that BASTA is a system that is well thought through with directions well anchored to laws and rules in the chemical area, that with a relatively good result can be applied to a real case. Yet, the system has its lacks. To enable an improvement of the system a number of points of improvements of BASTA was brought out. In the finishing chapter of this report a few different studies are being suggested that can be made in the future to further evaluate BASTA.
Keywords: Annan samhällsbyggnadsteknik; Other Civil Engineering